Analysis Shelf Life And Hedonic Test Original Kemojo With Purple Sweet Potato Kemojo - Gea, Selvi Yana; Elida, Elida; Syarif, Wirnelis; Anggraini, Ezi (Universitas Negeri Padang, 2024)
Kemojo is a traditional Riau cake formed like a frangipani flower, with a soft, green inner texture, non-porous, dense, but slightly dry outside, and a brownish hue. Kemojo is a traditional cuisine that includes wheat flour, eggs, granulated sugar, margarine, coconut milk, and pandan leaves. It is frequently served at weddings, circumcisions, fasting, and Eid. The purpose of this study was to examine the shelf life and hedonic test of traditional kemojo cake with purple sweet potato kemojo cake in terms of color, aroma, texture, and taste. The approach used is a hybrid method, which integrates qualitative and quantitative data. According to the study, the original kemojo cake and purple sweet potato kemojo cake have a shelf life of 3 days at room temperature (23˚C to 29˚C) with a closed ivory box. The hedonic test analysis results for the original kemojo cake and purple sweet potato kemojo cake were collected by administering a questionnaire to 50 consumer panelists and comparing the t-count to the t-table. If the t-count exceeds the t-table, then the hypothesis is accepted. If the t-count is less than the t-table, Ho is rejected. Specifically, color 3.256 ≥ 2.009, aroma 1.373 ≤ 2.009, texture 3.107 ≥ 2.009, and taste 697 ≤ 2.009. The data analysis results reveal a significant difference in color and texture preferences between the original kemojo cake and the purple sweet potato kemojo cake. The aroma and taste of the classic kemojo cake and the purple sweet potato kemojo cake are comparable.